2019
DOI: 10.25301/jpda.283.113
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Reliability of Rugoscopy for Identification of Gender

Abstract: METHODOLOGY: A sample size of 456 individuals aged between 15 and 55 years fulfilling inclusion and exclusion criteria were recruited for the study. The shapes and size of rugae were evaluated on dental casts by classification given by the Kapali et al and Thomas et al respectively. Chi-square test was used to see gender dimorphism in rugae shapes and Mann Whitney U test was used for gender dimorphism in rugae size. A p-value of < 0.05 was considered significant. The equation given by Bharath et al. was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Significant dimorphism of gender was observed while comparing the different shapes of rugae and the reliability of gender prediction by rugoscopy was 45.6%. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…Significant dimorphism of gender was observed while comparing the different shapes of rugae and the reliability of gender prediction by rugoscopy was 45.6%. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…A Study done in the Karachi population reported that common rugae pattern observed in males was wavy compared to curved pattern in females and they observed significant gender dimorphism in the size of secondary rugae (23) . Kolude et al discovered that Nigeria's Yoruba community had more wavy and straight patterns while the Igbo's of the same country had more curved and circular patterns (7) .…”
Section: Variations In Shapesmentioning
confidence: 99%